PERCEPTION TOWARDS FOOD CHOICE AMONG LOW-INCOME FACTORY WORKER PARENTS OF PRE-SCHOOL CHILDREN IN NORTHERN THAILAND: A QUALITATIVE STUDY - Wungrath, Jukkrit; Chanwikrai, Yupa; Khumai, Nuttida; Sutan, Piyawat (Malaysian Journal of Public Health Medicine, 2022)
Balanced and healthy eating habits in children may be one of the most important determinants of human health as well as good growth and development booster. Multiple factors in various contexts influence the formation of eating choices in childhood. To promote healthy food choices, it is necessary to understand the factors influencing food choices in pre-school children. Parents have been acknowledged to be an important factor impacting their children’s eating habits. This study investigates parents’ perspectives on children’s food choices. The study was conducted utilizing in-depth interviews using two focus groups. The participants included 44 parents (32 participants and 12 additional participants) of children aged between 2 and 5 years who work in the factory and live in a rural area of Hang Chat district, Lampang province, Thailand. Participants were recruited with the assistance of CCCs staff followed the inclusion ceriterias .Participants were given a list of potential factors and asked to identify the top five factors influencing their child’s eating choices. The responses were debated in a group. The discussion was recorded for later analysis. The results demonstrated that family income, child’s dietary preferences, peer influence, food advertising/marketing, parental nutritional knowledge, and food availability in the markets or shops were ranked as the most influential factors. This study highlights new and essential topics for future research and may help develop parent-child interventions to improve good eating habits in pre-school children.